Small banks and local economic development - Iftekhar Hasan; Phil Molyneux; Ru Xie; Hendrik Hakenes (Bank of Finland, 2014)
This paper discusses the effects of small banks on economic growth. We first theoretically show that small banks operating at a regional level can spur local economic growth. As compared with big interregional banks, small regional banks are more effective in promoting local economic growth, especially in regions with lower initial endowments and severe credit rationing. We then test the model predictions using a sample of German banks and corresponding regional statistics. We find that small regional banks are more important funding providers in regions with low access to finance. The empirical results support the theoretical hypotheses.
URN:NBN:fi:bof-20140807597
Keywords: G21; O16; R11; 330; small banks; regional economic growth